2018
DOI: 10.7554/elife.35224
|View full text |Cite
|
Sign up to set email alerts
|

Dual roles for ATP in the regulation of phase separated protein aggregates in Xenopus oocyte nucleoli

Abstract: For many proteins, aggregation is one part of a structural equilibrium that can occur. Balancing productive aggregation versus pathogenic aggregation that leads to toxicity is critical and known to involve adenosine triphosphate (ATP) dependent action of chaperones and disaggregases. Recently a second activity of ATP was identified, that of a hydrotrope which, independent of hydrolysis, was sufficient to solubilize aggregated proteins in vitro. This novel function of ATP was postulated to help regulate proteos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
88
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 80 publications
(93 citation statements)
references
References 63 publications
4
88
0
1
Order By: Relevance
“…In turn, this determines the composition and function of a given LLPS droplet, resulting in operational heterogeneity across a cell population. An unexpected factor that antagonizes protein aggregation or accumulation in MLOs is ATP, which was recently shown to act as a hydrotrope that destabilizes aggregated proteins, such as those found in the nucleolus, independently of its role as an energy source (Hayes, Peuchen, Dovichi, & Weeks, ; Patel et al, ; Rice & Rosen, ).…”
Section: Self‐organizing Membraneless Organelles and The Role Of Rnamentioning
confidence: 99%
See 1 more Smart Citation
“…In turn, this determines the composition and function of a given LLPS droplet, resulting in operational heterogeneity across a cell population. An unexpected factor that antagonizes protein aggregation or accumulation in MLOs is ATP, which was recently shown to act as a hydrotrope that destabilizes aggregated proteins, such as those found in the nucleolus, independently of its role as an energy source (Hayes, Peuchen, Dovichi, & Weeks, ; Patel et al, ; Rice & Rosen, ).…”
Section: Self‐organizing Membraneless Organelles and The Role Of Rnamentioning
confidence: 99%
“…in the nucleolus, independently of its role as an energy source (Hayes, Peuchen, Dovichi, & Weeks, 2018;Patel et al, 2017;Rice & Rosen, 2017).…”
Section: Figurementioning
confidence: 99%
“…2C, fig. S8, and table S7) showing on a proteome-wide scale that ATP hydrolysis is not the main factor for ATP-mediated solubilization and suggesting that previous findings based on fluorescently tagged nucleolus markers FBL and NPM1 cannot be generalized 36 .…”
mentioning
confidence: 79%
“…Due to high demand, the turnover rate of ATP is estimated to be less than one minute in yeast and metazoans (Mortensen, Thaning et al, 2011, Takaine, Ueno et al, 2019). In addition to its role as energy currency, recent studies reported that ATP may influence the balance between the soluble and aggregated states of proteins, suggesting that proteostasis is maintained by energy-dependent chaperones and also by the property of ATP as a hydrotrope to solubilize proteins (Hayes, Peuchen et al, 2018, Patel, Malinovska et al, 2017). Recent proteomic analyses demonstrated that many cellular proteins are insoluble at submillimolar ATP concentrations and become soluble at ATP concentrations > 2 mM (Sridharan, Kurzawa et al, 2019); however, it currently remains unclear whether ATP-dependent protein solubilization/desolubilization play any significant roles in cell physiology.…”
Section: Introductionmentioning
confidence: 99%